Analysis Of The Causes And Consequences Of Work Accidents In Multi-Storey Building Construction - Ilham Arista Harahap; I Nyoman Dita Pahang Putra (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
The construction of multi-storey building projects is one of the developments that also carries a high risk in terms of work accidents. Work accidents in the construction sector are actually the result of risk mitigation that is not well targeted. Based on data from BPS in 2014, there were 105,383 cases of work accidents recorded. The work accident data is dominated by the construction sector. The objective of this study is to examine the factors contributing to workplace accidents in construction projects involving multi-storey buildings. The stages of this research are a literature study to determine the variables to be used, followed by designing a research questionnaire and then collecting data by distributing questionnaires to contractors and supervising consultants from several construction projects. Data processing using questionnaire results is quantitative with the help of Microsoft Excel, IBM SPSS 23 and SmartPLS programs. The data obtained were subjected to multivariate analysis using research instrument tests and classical assumption tests, then outer model and inner model tests were carried out so that it could be seen which independent variables had the most influence. The discussion in this research is explained through Pearson correlation analysis, multivariate analysis and SEM analysis. The outcome of this study aims to identify the factors that contribute to the outcomes of work accidents, namely human causal factors have a positive influence on serious work accidents, the higher the causal factors caused by humans, the higher the risk of serious work accidents occurring